Controlling of growth performance, lipid deposits and fatty acid composition of chicken meat through a probiotic, Lactobacillus johnsonii during subclinical Clostridium perfringens infection. Issue 1 (December 2017) - Wang, Hesong; Ni, Xueqin; Liu, Lei; Zeng, Dong; Lai, Jing; Qing, Xiaodan; Li, Guangyao; Pan, Kangcheng; Jing, Bo
Abstract Background Meat is considered as a major source of polyunsaturated fatty acid (PUFA) which is essential for humans, therefore its lipid level and fatty acid composition have drawn great attention. As no clinical sign can be found in chicks subclinically infected byClostridium perfringens (CP), the meat may be purchased and eaten. The objective of the present study was to determine whetherLactobacillus johnsonii (LJ) can control the CP-caused impact on growth, lipid levels, fatty acid composition and other flavor or nutritional quality in the meat. Methods 480 one-day-old chicks were divided into four groups and fed with basal diet (control and CP group). Supplemented with 1 × 105 (L-LJ) and 1 × 106 (H-LJ) colony-forming unit (cfu), CP diet was fed for 42 days. From day 19 to 22, birds of CP and LJ groups were administered with CP twice per day and the control was administered with liver broth. Results LJ-treated chickens were free from negative influences on growth performance and significant decrease of abdominal fat deposit., LJ inhibited CP-caused shearing force and drip loss increase and pH 40 min and 24 h decrease after sacrifice. In addition, LJ exhibited a positive effect on muscle lipid peroxidation by significantly increasing SOD, CAT and GSH-Px activity and decreasing MDA level. Besides, LJ attenuated the decrease of intramuscular fat, total cholesterol and triglyceride contents caused by CP infection. However, levels of total protein and most of amino acids were not changed. CP infection decreased C18:3n-3 (α-LA), C20:4n-6, C20:5n-3(EPA), C22:4n-6, C22:5n-3, C22:6n-3(DHA), total PUFA, n-3 PUFA and PUFA:SFA ratio and increased C14:0, total SFA and n-6:n-3 ratio. LJ was found to protect the muscle from these changes. Meanwhile, the 28-day gut permeability level was higher in CP group. Conclusions These findings suggest that CP may affect the growth performance of chicks and negatively influence lipid content and fatty acid composition in chicken meat. Meanwhile, LJ treatment may be effective in controlling these changes by reducing the increased gut permeability caused by CP subclinical infection.